Diurnal Patterns of Testosterone and Cortisol Metabolites in Fecal of Javan Gibbons (Hylobates moloch) in Captivity - PUDJI ASTUTI; TUTY LASWARDI YUSUF; ERIC HAYES; HERA MAHESHWARI; LUTHFIRALDA SJAHFIRDI; DONDIN SAJUTHI (Bogor Agricultural University, Indonesia, 2006)
The aims of this research were to determine diurnal patterns of testosterone and cortisol metabolites to predict the testis functional status. In this study, fecal testosterone and cortisol were quantified in 77 samples from three male Hylobates moloch during a course of three months period. These data showed that the highest concentration of fecal testosterone occured at 18.00-06.00 (23.61 ng/g dried feces), then declined gradually. The lowest concentration was in the evening (5.54 ng/g dried feces). Our tests showed that there was a decrease in the mean testosterone concentration from 06.00-10.00 to 10.00-14.00 to 14.00-18.00. For cortisol, the highest concentration occured at 06.00-10.00 (597.84 ng/g dried feces), then decline gradually in the evening (225.73 ng/g dried feces). Key words: Hylobates moloch, feces, testosterone, cortisol, diurnal pattern